Prosedur Penyelesaian Hutang Piutang Antar Bank Dengan Sistem Semi Otomasi Kliring Lokal (SOKL) pada Bank Negara Indonesia (Persero) Tbk” - Hariyanti Hariyanti (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
In the process of carrying out clearing activities, obstacles often arise that are faced by the bank, so that this can hinder the smooth running of the clearing process itself. So, to avoid these things, banks are required to provide explanations to customers so that they are more careful with each document that is cleared. So that in this way you can reduce the risks that may occur before the Bank.